2009
DOI: 10.3199/iscb.4.65
|View full text |Cite
|
Sign up to set email alerts
|

Hybridity and relationship between Chrysanthemum shiwogiku Kitam. and C. vestitum (Hemsl.) Stapf.

Abstract: ABSTRACT. Artificial crosses between the Japanese, octoploid Chrysanthemum shiwogiku Kitamura and Chinese, hexaploid C. vestitum (both Asteraceae-Anthemideae) produced 48 hybrids out of 181 germinated plants grown up to the mature stage. The hybrids showed more or less intermediate in morphological character between the two parents and somewhat more close to C. vestitum in white-color ligule flowers inherited. The chromosome numbers in 19 out of 48 hybrids studied varied from 2n=63 to 81 with various aneuploid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A. fruticulosa. As far as our literature review could ascertain, all karyological investigations of the genus Ajania reported solely chromosome number of taxa and the common base chromosome number was found to be x = 9 with ploidy level ranging from diploid to decaploid (Kondo et al 1998, Garcia et al 2006, Zhao et al 2007, 2009, Abd El‐Twab and Kondo 2009). Recently, molecular phylo genetic analysis of Ajania and allied genera based on ITS and ETS sequence data has been performed and a close relationship of Ajania to Chrysanthemum L. was inferred (Zhao et al 2010).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…A. fruticulosa. As far as our literature review could ascertain, all karyological investigations of the genus Ajania reported solely chromosome number of taxa and the common base chromosome number was found to be x = 9 with ploidy level ranging from diploid to decaploid (Kondo et al 1998, Garcia et al 2006, Zhao et al 2007, 2009, Abd El‐Twab and Kondo 2009). Recently, molecular phylo genetic analysis of Ajania and allied genera based on ITS and ETS sequence data has been performed and a close relationship of Ajania to Chrysanthemum L. was inferred (Zhao et al 2010).…”
mentioning
confidence: 87%
“…Tzvel. (Abd El‐Twab and Kondo 2009). Garcia et al (2006) reported the presence of B chromosomes in A. fruticulosa (2n = 36 + 4B), which was not found in A. semnanensis .…”
Section: Karyotype Analysismentioning
confidence: 99%